1994
DOI: 10.1159/000176530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thrombolytic Therapy on Postinfarction Myocardial Ischemia

Abstract: In patients with acute myocardial infarction a substantial reduction in mortality can be achieved by early intravenous thrombolytic therapy. The beneficial effect of thrombolysis on left ventricular function is relatively small, and it seems unlikely that this minor improvement alone can be responsible for the reduction in cardiac death. So far it has not been clearly established how thrombolytic therapy affects postinfarction myocardial ischemia. From studies evaluating ST segment changes on exercise testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Finally, it has been suggested that in the early in-hospital postinfarction period, tran sient myocardial ischemia may be related more to supply than to demand, unlike the pathophysiological mecha nism later on [11], How thrombolytic therapy affects postinfarction tran sient myocardial ischemia has not been clearly estab lished. From the data available, however, it appears justi fied to propose that thrombolytic treatment given for an AMI results in the detection of less myocardial ischemia [12,[23][24][25], When serial Holter recordings are performed in the same environmental milieu, the prevalence of transient myocardial ischemia does not seem to change during the first year after a first myocardial infarction [26]. If, how ever, the results of early in-hospital (6 days) and late outof-hospital (1-3 months) ambulatory monitorings are com pared, transient ischemic episodes are shown to be signifi- Table 2.…”
Section: Prevalence and Characteristics Of Transient Myocardial Ischemiamentioning
confidence: 99%
“…Finally, it has been suggested that in the early in-hospital postinfarction period, tran sient myocardial ischemia may be related more to supply than to demand, unlike the pathophysiological mecha nism later on [11], How thrombolytic therapy affects postinfarction tran sient myocardial ischemia has not been clearly estab lished. From the data available, however, it appears justi fied to propose that thrombolytic treatment given for an AMI results in the detection of less myocardial ischemia [12,[23][24][25], When serial Holter recordings are performed in the same environmental milieu, the prevalence of transient myocardial ischemia does not seem to change during the first year after a first myocardial infarction [26]. If, how ever, the results of early in-hospital (6 days) and late outof-hospital (1-3 months) ambulatory monitorings are com pared, transient ischemic episodes are shown to be signifi- Table 2.…”
Section: Prevalence and Characteristics Of Transient Myocardial Ischemiamentioning
confidence: 99%